Human immunodeficiency virus type 1 infection associated dementia - Custodio, Nilton (2006)
Dementia associated to human immunodeficiency virus infection (DHIV) is an entity distinguished by three main signs -cognitive, behavioral and motor symptoms- which generate serious difficulties in the functional capacity of the patient. The multiple denominations generate confusion and diagnostic difficulties. In spite of controversy in DHIV incidence, it is clear that more than 90% of patients with AIDS has compatible neuropathological anormalities with DHIV. The pathogenic mechanisms involve complex interactions between the HIV and the brain cells generating two inclusive paths, inflammatory and non inflammatory, that produce neurotoxic and chemotactic factors, inductors of apoptosis that lead to neuro-glial disruption probably responsible of injury and/or neuron cell death, that finally would lead to accelerated neurodegeneration phenomenon. Symptoms are subcortical dementia, mental sluggishness, walking difficulties and depression. Diagnosis is essentially clinical and by exclusion. The HIV Dementia Scale (HDS) and the International HIVD Scale (IHDS) are of practical usefulness as initial screening tests. Treatment should include the combination of antiretrovirals and neuroprotectors. We conclude that DHIV is a devastating complication of HIV infection that should have early recognition.